The molluscs of the intertidal algal turf in the Azores - Ávila, Sérgio P. (2011)
The molluscan fauna of the high intertidal algal turf on the island of Pico (Azores) was studied in order to complement existing descriptions of the intertidal biota on these islands. A total of 15,275 specimens belonging to 19 species were found. Five species, the gastropods Alvania mediolittoralis Gofas, 1989, Omalogyra atomus (Philippi, 1841), Pisinna glabrata (Megerle von Muhlfeld, 1824) and Skeneopsis planorbis (Fabricius 0., 1780), and the bivalve Lasaea adansoni (Gmelin, 1791), account for 98% of the total number of specimens, P. glabrata itself being responsible for 46% of all specimens. In places where patellid limpets are absent, Ihe algal turf extends higher in the intertidal zone. In such places, three very abundant molluscan species characterize molluscan assemblages in the algal turf: Lasaea adansoni, Skeneopsis planorbis and Pisinna glabrata, Lasaeo adansoni and Skeneopsis planorbis virtually disappear in the transition from algal lurf to algal fronds, the only (very) abundant species being P. glabrata and, with less importance, Omalogyra atomus and Sinezona cingulata (Costa O.G., 1861).